Peroxide-Free Co(OAc)2-Catalyzed Radical Addition of sp3 C–H Bonds to Alkynes - Zhang, Min; Zhao, Yun; Chen, Wanzhi (Synthesis, 2017)
Cobalt-catalyzed radical addition of C–H bonds adjacent to an oxygen atom towards alkynes is described. The reaction proceeded at 60 °C without using additional radical initiators, and leads to 2-vinyl ether derivatives in good yields.
Keywords: cobalt catalysis; radical addition; alkyne; tetrahydrofuran